EDUCATOR RESPONSIBILITY AND FLEXIBILITY - Torayeva Sayyora Sattorovna (Scholar Express Journal, 2023)
In the article the quality of education is the priority, the intellectual potential of personnel, the level of formation of the characteristics of professional responsibility,It is reported that it is difficult for a child to adapt to society without education, that a developing person is necessary for the formation of social attitudes, values, and the position of active activity in society
Keywords: regulatory and legal; professional knowledge and skills; intellectual potential